Peningkatan Hasil Belajar Matematika Materi Pecahan melalui Model Pembelajaran Kontekstual bermuatan Etnomatematika pada Siswa Kelas III - Ermawati, Dewi; Sri Legowo, Yogi Ageng; Fakih, Moh (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2023)
Low mathematics learning outcomes, low student learning activity in learning mathematics and low teacher skills in teaching because the teacher only uses the lecture learning model. This type of research is classroom action research. This study aims to improve the learning outcomes of mathematics in fraction material in class III students of Lerep 04 Public Elementary School in the 2022/2023 academic year through the application of an ethnomathematics-laden contextual model. The subjects of this study were 21 students of class III SDN Lerep 04, consisting of 8 boys and 13 girls. This research was conducted on 23 February - 4 March 2023 at SDN Lerep 04. The research instruments were (1) tests to measure class III student learning outcomes, (2) non-tests in the form of observation sheets to observe teacher teaching skills and student learning activities in learning. Data analysis techniques using quantitative and qualitative data analysis. The results of the study show that the ethnomathematics-loaded contextual loaded model can improve student learning outcomes. This is evidenced by the acquisition in the first cycle of learning outcomes of 53% (11 students) completing KKM, teaching teacher skills 2.32 (good enough), and student learning activities 57% (12 students). Cycle II learning outcomes by 67% (14 students) complete KKM, teacher skills 2.72 (Good), and student learning activities by 71% (15 students). Cycle III learning outcomes were 86% (18 students) complete KKM, teacher teaching skills were 3.36 in the Very Good category, as well as student learning activities 85% (18 students) in the Good category.